Semantic Relations Cause Interference in Spoken Language Comprehension When Using Repeated Definite References, Not Pronouns - Peters, Sara A.; Boiteau, Timothy W.; Almor, Amit (Frontiers in Psychology, 2016)
The choice and processing of referential expressions depend on the referents’ status within the discourse, such that pronouns are generally preferred over full repetitive references when the referent is salient. Here we report two visual-world experiments showing that: (1) in spoken language comprehension, this preference is reflected in delayed fixations to referents mentioned after repeated definite references compared with after pronouns; (2) repeated references are processed differently than new references; (3) long-term semantic memory representations affect the processing of pronouns and repeated names differently. Overall, these results support the role of semantic discourse representation in referential processing and reveal important details about how pronouns and full repeated references are processed in the context of these representations. The results suggest the need for modifications to current theoretical accounts of reference processing such as Discourse Prominence Theory and the Informational Load Hypothesis.